Molecular Delineation of Species in the Coral Holobiont - Stat, Michael; Baker, A.; Bourne, D.; Correa, A.; Forsman, Z.; Huggett, M.; Pochon, X.; Skillings, D.; Toonen, R.; van Oppen, M.; Gates, R. (2012)
The coral holobiont is a complex assemblage of organisms spanning a diverse taxonomic range including a cnidarian host, as well as various dinoflagellate, prokaryotic and acellular symbionts. With the accumulating information on the molecular diversity of these groups, binomial species classification and a reassessment of species boundaries for the partners in the coral holobiont is a logical extension of this work and will help enhance the capacity for comparative research among studies. To aid in this endeavour, we review the current literature on species diversity for the three best studied partners of the coral holobiont (coral, Symbiodinium, prokaryotes) and provide suggestions for future work on systematics within these taxa. We advocate for an integrative approach to the delineation of species using both molecular genetics in combination with phenetic characters. We also suggest that an a priori set of criteria be developed for each taxonomic group as no one species concept or accompanying set of guidelines is appropriate for delineating all members of the coral holobiont. © 2012 Elsevier Ltd.